Prevalence of recurrent oral lichen planus among patients - a retrospective study - SANGAR, SIVESH; VADIVEL, JAYANTH KUMAR; RAMANATHAN, VISALAKSHI (The journal of contemporary issues in business and government, 2021)
To determine the prevalence of recurrent oral lichen planus among patients with oral lichen planus visiting the outpatient Department of Oral Medicine and Radiology, Saveetha Dental Hospital, Chennai.Objective:The purpose of the study was to determine the prevalence of recurrent oral lichen planus among patients with oral lichen planus visiting the outpatient Department of Oral Medicine and Radiology, Saveetha Dental Hospital, Chennai. Materials and Methods:A hospital based cross-sectional study was conducted by collecting data by reviewing patients data and analysing the data of 86000 patients between June 2019 and March 2020. 59 patients with oral lichen planus attending Saveetha Dental Hospital, Chennai were included in the study. The data were gathered through semi- closed ended questionnaires and clinical examinations.Results showed that the recurrence of oral lichen planus in female patients to be 57% and the prevalence of recurrence in male patients to be 50%. Data analysis was done using a chi square analysis between gender with prevalence of recurrent oral lichen planus (chi- square-0.563;df-1;p-0.461) we found the results were statistically not significant(P>0.05) which implies that there was no association between the gender and recurrence of Oral lichen planus. Conclusion:Within the limits of the study, patients who have a recurrence of oral lichen planus seem to be more of the reticular and erosive variants of OLP. It remains to be seen if the erosive OLP has a tendency to develop into oral malignancies.